Răspuns :
x-y=36
x/y= 2/5
5x=2y
x-y=36 | * (-2)
5x-2y=0
-2x+2y=-72
5x-2y=0
3x=-72 | *(-1) => x= 24
=> 5 * 24 = 2y => y= 120/2=> y= 60
x/y= 2/5
5x=2y
x-y=36 | * (-2)
5x-2y=0
-2x+2y=-72
5x-2y=0
3x=-72 | *(-1) => x= 24
=> 5 * 24 = 2y => y= 120/2=> y= 60
a-b=36 => a=b+36 sau b=a-36
[tex]b = \frac{2a}{5} [/tex]
[tex]a - \frac{2a}{5} = 36[/tex]
[tex] \frac{5a}{5} - \frac{2a}{5} = \frac{180}{5} [/tex]
deoarece avem același numitor, nu-l vom mai mai scrie.
5a-2a=180
3a=180|:3
a=60
b=60-36=24
[tex]b = \frac{2a}{5} [/tex]
[tex]a - \frac{2a}{5} = 36[/tex]
[tex] \frac{5a}{5} - \frac{2a}{5} = \frac{180}{5} [/tex]
deoarece avem același numitor, nu-l vom mai mai scrie.
5a-2a=180
3a=180|:3
a=60
b=60-36=24